Konstruksi Hukum Berpindahnya Hak Perwalian Sebab Masafatul Qashri - Fashihuddin Arafat (MASADIR: Jurnal Hukum Islam, 2021)
Abstract : In marriage, the existence of a marriage guardian is an element that must be fulfilled for the sake of the marriage. If the guardian is unable to attend the wedding due to a long distance, for example the distance allowed for qashar prayer (masafatul qashri). What is the status of guardianship rights? This study aims to determine whether guardianship rights can be transferred to other people due to long distances (masafatul qashri). With library research methods with secondary data sources. The results show that the Shafi'i school says if the aqrab guardian is unknown or unseen (masafatul qashri) then the guardianship rights shift to the guardian judge. Meanwhile, the Hambali School says that if the wali aqrab's whereabouts are unknown or unseen, then his guardianship rights can be transferred to wali ab'ad. The transfer of guardianship rights due to masafatul qashri is still very relevant. Because the long distance does not become a barrier for a guardian to marry off his child. The legal solution is in Article 12 paragraph (4) of the Regulation of the Minister of Religion No. 20 of 2019 concerning Marriage Registration. Keywords: Guardianship Rights, Masafatul Qashri